2020
DOI: 10.3390/rs12244081
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Tree Crown Extraction from UAS Multispectral Imagery for the Detection of Bark Beetle Disturbance in Mixed Forests

Abstract: Multispectral imaging using unmanned aerial systems (UAS) enables rapid and accurate detection of pest insect infestations, which are an increasing threat to midlatitude natural forests. Pest detection at the level of an individual tree is of particular importance in mixed forests, where it enables a sensible forest management approach. In this study, we propose a method for individual tree crown delineation (ITCD) followed by feature extraction to detect a bark beetle disturbance in a mixed urban forest using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 86 publications
0
35
0
Order By: Relevance
“…However, a small proportion of ground objects that are not classified as tea in the ground multispectral images can affect the final quality of the parameter monitoring results. In order to reduce the influence of soil and shadow noise and improve the accuracy of the final quality parameter monitoring results, this study used the EXG index to effectively distinguish the background of green vegetation and soil for image enhancement [31,[79][80][81][82]. The Ostu method was used for image segmentation [32,[83][84][85][86] to enable the effective extraction of the tea areas from the original image that contains other features.…”
Section: Ground Multispectral Imagesmentioning
confidence: 99%
“…However, a small proportion of ground objects that are not classified as tea in the ground multispectral images can affect the final quality of the parameter monitoring results. In order to reduce the influence of soil and shadow noise and improve the accuracy of the final quality parameter monitoring results, this study used the EXG index to effectively distinguish the background of green vegetation and soil for image enhancement [31,[79][80][81][82]. The Ostu method was used for image segmentation [32,[83][84][85][86] to enable the effective extraction of the tea areas from the original image that contains other features.…”
Section: Ground Multispectral Imagesmentioning
confidence: 99%
“…PPCs were used in two studies. Minařík et al [100] used PPCs collected through a UAV to identify and delineate canopies in an urban mixed forest. They analyzed the effect of point density on individual tree delineation and found an OA of 82% in crown detection from a PPC.…”
Section: Aerial Imagerymentioning
confidence: 99%
“…Through PPCs generated from UAV flights, metrics, such as tree height and crown data, can be analyzed [99]. Minařík et al [100] found that, when processing PPCs, point density is more important than the selection of a given processing method, recommending a range between 10 and 85 points/m 2 for tree canopy identification and delineation in urban environments, while Birdal et al [99] suggested at least 40 points/m 2 for proper height characterization.…”
Section: Aerial Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing is a proven technology for pest monitoring and damage assessment over large areas. Many studies have used remotely sensed data with various spatial resolutions to detect and assess forest insect infestations, based on the analysis of spectral responses of trees to the biophysical phenomena such as water stress caused by insect attack [13][14][15][16][17][18][19]. Over the years, a number of spectral indices (such as the Normalised Difference Vegetation Index or NDVI, the Normalised Burn Ratio or NBR, the Moisture Stress Index or MSI, the Enhanced Wetness Difference Index or EWDI, and the Leave Area Index or LAI) have been used for the detection and differentiation of insects and diseases using multispectral and hyperspectral data with different spatial resolutions.…”
Section: Introductionmentioning
confidence: 99%